Dissecting the 2007-2009 Real Estate Market Bust: Systematic Pricing Correction or Just a Housing Fad? - Daniele Bianchi; Massimo Guidolin; Francesco Ravazzolo (Norges Bank, 2013)
We use Bayesian methods to estimate a multi-factor linear asset pricing model characterized by structural instability in factor loadings, idiosyncratic variances, and factor risk premia. We use such a framework to investigate the key differences in the pricing mechanism that applies to residential vs. non-residential (such as office space, industrial buildings, retail property) real estate investment trusts (REITs). Under the assumption that the subprime crisis has had its epicentre in the housing/residential sector, we interpret any differential dynamics as indicative of the propagation mechanism of the crisis towards business-oriented segments of the US real estate market. We find important differences in the structure as well as the dynamic evolution of risk factor exposures across residential vs. non-residential REITs. An analysis of cross-sectional mispricings reveals that only retail, residential, and mortgage-specialized REITs were over-priced over the initial part of our sample, i.e., 1999-2006. Moreover, residential-driven real estate has structural properties that make it different from non-residential assets.
hdl:11250/2496683
Keywords: G11; C53; 330; multi-factor models; real estate; mispricing; real estate investment trusts